Transferability of an HGM wetland classification scheme to a longitudinal gradient of the central Appalachian Mountains: initial hydrological results - Cole, Charles Andrew; Cirmo, Christopher P.; Wardrop, Denice Heller; Brooks, Robert P.; Peterson-Smith, Jessica (Wetlands (Wilmington, N.C.), 2008)
The fundamental role of hydrology in determining HGM classification and function leads to the assumption that any test of regionalization might do well to begin with a comparison of hydrologic variation within regional subclasses across a geographical or landscape continuum. This paper deals with only the basic hydrologic comparisons between New York, Pennsylvania, and Virginia for similarly classified wetlands in all three regions. Water levels for headwater floodplain wetlands varied substantially between the New York region and the Pennsylvania and Virginia regions; the latter regions were very similar. The same pattern was evident for slope wetlands across the three regions, but there was no significant difference in water levels for riparian depressions. Based upon the hydrologic data alone, it seems that applying the classification outside of central Pennsylvania had mixed results; it worked well south to Virginia and less well north to New York. One substantial influence in New York was the presence of beaver (Castor canadensis) that greatly influenced almost every watershed we worked in. Furthermore, climate differences between the three regions may also have a large impact – the New York sites were subject to much more snow than sites further south.